What general practitioners said about the palliative care case conference in residential aged care: An Australian perspective. Part 2. (February 2015) - Tuckett, Anthony; Parker, Deborah; Clifton, Karen; Walker, Helen; Reymond, Elizabeth; Prior, Teresa; Jenkin, Peter; Israel, Fiona; Greeve, Kim; Glaetzer, Karen
Abstract : Objective: To examine the views of general practitioners (GPs) on providing a palliative approach in residential aged care and in particular their experiences with the palliative care case conference. Background: The national project sought to implement and evaluate a comprehensive evidence-based palliative approach in residential aged care. Methods: A purposive sample of 11 GPs across Western Australia (2), South Australia (6) and Queensland (3) participated in face-to face, semi-structured interviews. Qualitative content analysis was used to generate the core categories. Results: The evaluation by the GPs of the palliative care case conference in residential aged care is explained through three core themes: people, place, and performance. Understanding what GPs say about the performance or 'doing' a palliative care case conference can purposefully inform practice and policy. What GPs say about the people involved and the place in which they work, namely the residential aged care facility, is provided in Part I of this two part series. Conclusion: The views of GPs, on providing a palliative approach in residential aged care facilitates, offer a critical reflection on current practices and systems.